Predicting freedom from clinical events in non-ST-elevation acute coronary syndromes: the Global Registry of Acute Coronary Events. Issue 11 (25th February 2009) - Brieger, D; Fox, K A A; FitzGerald, G; Eagle, K A; Budaj, A; Avezum, Á; Granger, C B; Costa, B; Anderson, F A; Steg, Ph G; ,
Abstract : Objective: To identify patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) with a low likelihood of any adverse in-hospital event. Design, setting and patients: Data were analysed from 24 097 patients with NSTEMI or unstable angina included in the Global Registry of Acute Coronary Events (January 2001 to September 2007). Main outcome measures: In-hospital events were myocardial infarction, arrhythmia, congestive heart failure or shock, major bleeding, stroke or death. Two-thirds of the patients were randomly chosen for model development and the remainder for model validation. Multiple logistic regression identified predictors of freedom from an in-hospital event, and a Freedom-from-Event score was developed. Results: Of the 16 127 patients in the model development group, 19.1% experienced an in-hospital adverse event. Fifteen factors independently predicted freedom from an adverse event: younger age; lower Killip class; unstable angina presentation; no hypotension; no ST deviation; no cardiac arrest at presentation; normal creatinine; decreased pulse rate; no hospital transfer; no history of diabetes, heart failure, peripheral arterial disease, or atrial fibrillation; prehospital use of statins, and no chronic warfarin. In the validation group, 18.6% experienced an adverse event. The model discriminated well between patients experiencing an in-hospital event and those who did not in both derivation and validation groups (c-statistic = 0.77 in both). Patients in the three lowest risk deciles had a very low in-hospital mortality (<0.5%) and an uncomplicated clinical course (>93% event-free in hospital). The model also predicted freedom from postdischarge events (death, myocardial infarction, stroke; c-statistic = 0.77). Conclusions: The GRACE Freedom-from-Event score can predict the in-hospital course of NSTE-ACS, and identifies up to 30% of the admitted population at low risk of death or any adverse in-hospital event.